A combination of pre-infusion serum ferritin, CRP and IL-6 predicts outcome in relapsed/refractory multiple myeloma patients treated with CAR-T cells - Liu, Yang; Jie, Xingxing; Nian, Li; Wang, Ying; Wang, Congyue; Ma, Jin; Jiang, Jingjing; Wu, Qingyun; Qiao, Jianlin; Chen, Wei; Cao, Jiang; Yan, Zhiling; et al. (Frontiers in Immunology, 2023)
Background: Chimeric antigen receptor - T (CAR-T) cell therapy has shown remarkable efficacy in patients with relapsed/refractory multiple myeloma (R/R MM). However, a subset of patients still experienced progression or relapse, and the predictors of prognosis are little known. We analyzed the inflammatory markers before CAR-T cell infusion, to clarify their correlation with survival and toxicity. Methods: This study involved 109 R/R MM patients who received CAR-T therapy between June 2017 and July 2021. Inflammatory markers, including ferritin, c-reactive protein (CRP), and interleukin-6 (IL-6) before CAR-T cell infusion were detected and then categorized by quartiles. Adverse events and clinical outcomes were compared between patients with upper quartile of inflammatory markers and patients with lower three quartiles. An inflammatory prognostic index (InPI) based on these three inflammatory markers was developed, patients were divided into 3 groups, progression-free survival (PFS) and overall survival (OS) were compared among the groups. Results: We found that the pre-infusion high ferritin (hazard ratio [HR], 3.382; P = .0007), high CRP (HR, 2.043; P = .044), and high IL-6 (HR, 3.298; P = .0013) were associated with inferior OS. The formula of the InPI score was based on these 3 variables. Three risk groups were formed: (good, 0 to 0.5 point; intermediate, 1 to 1.5 points; poor, 2 to 2.5 points). Median OS for patients with good, intermediate, and poor InPI was not reached, 24 months, and 4 months, respectively, and median PFS was 19.1 months, 12.3 months, and 2.9 months, respectively. In the cox proportional hazards model, poor InPI remained an independent prognostic factor for PFS and OS. Spearman correlation analysis showed that pre-infusion ferritin and IL-6 levels positively correlated with the grade of CRS (P = .0369 and P = .0117, respectively). The incidence of severe CRS was higher in patients with high IL-6 compared with patients with low IL-6 (26% vs. 9%, P = .0405). Pre-infusion ferritin, CRP and IL-6 were positively correlated with each peak values within the first month after infusion. Conclusions: Our results suggest that patients with elevated inflammation markers before CAR-T cell infusion are more likely to have poor prognosis.